2020
DOI: 10.11591/ijece.v10i2.pp1736-1746
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive blood glucose monitoring system based on near-infrared method

Abstract: Diabetes is considered one of the life-threatening diseases in the world which need continuous monitoring to avoid the complication of diabetes. There is a need to develop a non-invasive monitoring system that avoids the risk of infection problems and pain caused by invasive monitoring techniques. This paper presents a method for developing a noninvasive technique to predict the blood glucose concentration (BCG) based on the Near-infrared (NIR) light sensor. A prototype is developed using a finger sensor based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Generally, spectrophotometers use halogen lamps as light sources with a lifetime of certain. In addition, there are filters/wavelengths that can be selected according to the desired examination [8][9] [10]. Of course, such a spectrophotometric tool has a fairly high price, with a limited lifetime of halogen lamps.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, spectrophotometers use halogen lamps as light sources with a lifetime of certain. In addition, there are filters/wavelengths that can be selected according to the desired examination [8][9] [10]. Of course, such a spectrophotometric tool has a fairly high price, with a limited lifetime of halogen lamps.…”
Section: Introductionmentioning
confidence: 99%
“…A summarized table of comparing previous works of PPG based NIBG with personalized models and this work is illustrated in Table 1 . Al-dhaheri et al 32 collected fifteen days of PPG signals from 10 healthy human subjects, where a linear regression model was trained from the first ten days and tested with the remaining five days of data. Rachim and Chung 17 built a PLSR model from data of every 10 min pre-carbohydrate-rich meals and every 20 min post-meal, for a total of 120 min from 12 healthy volunteers, trained by one day and tested on the next day.…”
Section: Introductionmentioning
confidence: 99%
“… References Recruited subjects Accuracy (zone A ratio of CEG) Training Rounds for modeling Time span between training and testing Input data Method Age of population V.P. Rachim et al 17 12 healthy subjects 100% ~ 20 1 day 24 features from PPG Linear partial least squares regression Not reported Al-dhaheri et al 32 10 healthy subjects > 90% > 30 Not reported PPG signal voltage Linear regression 20–36 Shu-jen Yeh et al 33 2 diabetes and 1 healthy subject 90% or less, subject dependent 3–4 day, with 15 min interval 1–13 days Temperature-modulated reflectance signal linear least square regression, retrieving training data for best model fitting 50–58 This work 30 diabetic subjects 100% (with auto-screening); 80% (w/o screening) 12 20–85 days PPG signal Deduction Learning 42–76 …”
Section: Introductionmentioning
confidence: 99%
“…However, achieve high safety living [6][7][8] for elderly and patients is challenged. Thus, healthcare monitoring/tracking for those people are vital [9]. According the World Health Organization (WHO) reports, the number of T2D patients is 422 million in 2014.…”
Section: Introductionmentioning
confidence: 99%